Aktivitas Debat Bahasa Inggris sebagai Solusi Permasalahan Komunikasi Interpersonal dan Pemikiran Kritis di Era Digital: Studi Kasus pada UKM UMSU Debating Society - Zuhdi, Abdurrahman (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2024)
Abstract : This study aims to analyze the role of English debate activities at the UMSU Debating Society in addressing interpersonal communication issues and developing students' critical thinking skills in the digital era. The approach used in this research is qualitative, with data collection techniques involving observation and interviews. The results show that debate activities serve as an effective solution in enhancing students' interpersonal communication skills by encouraging them to interact actively, listen critically, and provide constructive responses. Furthermore, debate activities also contribute to the development of students' critical thinking, where they are required to analyze, evaluate, and construct arguments based on valid evidence, as well as think logically and rationally. This study connects the findings with the Theory of Interpersonal Communication, Critical Thinking Theory, and Mass Communication and Social Media Theory, emphasizing the importance of effective communication and critical thinking in an increasingly digital world. Although technology and social media offer advantages in expanding the reach of debates, challenges related to unequal access to technology remain an issue that needs to be addressed. Overall, the UMSU Debating Society plays an important role in enhancing students' communication and critical thinking skills through English debate competitions that utilize social media and digital technology. Keyword : English Debate, Interpersonal Communication, Critical Thinking, Digital Technology, Social Media.